Game Mechanics: Sniper Simulator Game - Elbert Christoper Larosa; Matthew Kharli (Journal of Games, Game Art, and Gamification, 2018)
Popularity of game creates opportunity to everyone in developing a game that can be used to address any specific problem in many areas. In BINUS University International, for education purposes, game is not only being used as a tool/media to learn something, but it can also be used to develop student understanding on how the game mechanic of the games works. By understanding the mechanic of the games, hopefully it can help them in developing a game designed that can be used to address problems in their environment.